How to measure our impact on society? - Marc, Mojca (Dynamic relationships management journal, 2022)
The purpose of this paper is to help organizations when facing the challenge of measuring social impact of their activities. While examples of environmental effects’ analyses abound, that does not hold for the analysis of social impact. To illustrate how organizations can demonstrate their impact on society, we evaluate the activities of the Incredible Years (hereafter IY) parenting program using the social return on investment (SROI) approach, considering not only the direct impact of the program on children, but a broader range of outcomes for different stakeholders. We show that the monetized impacts of the program are about ten times higher than the costs of the program. The SROI as an evaluation approach is generally applicable to activities of profit and nonprofit organization, and serves as a reference to demonstrate the value of expected social impact to investors and funders. As such, SROI is a valuable tool not only to managers but to policy makers as well. We discuss the steps, data requirement, interpretation of results, and limitations of the social impact analysis.
Keywords: družbena odgovornost; management; social responsibility; sustainable development; trajnostni razvoj